Food Intake and Blood Levels of Mercury, Lead, and Cadmium Among Healthy Reproductive Aged Women (P18-024-19). (13th June 2019) - Kim, Keewan; Nobles, Carrie; Purdue-Smithe, Alexandra; Wactawski-Wende, Jean; Pollack, Anna; Freeman, Joshua; Alkhalaf, Zeina; Andriessen, Victoria; Radoc, Jeannie; Mumford, Sunni
Abstract: Objectives: Exposure to toxic metals mostly occurs via contaminated food intake. Though toxic metals adversely affect reproductive health, common food sources among reproductive aged women are less understood. We addressed this gap among healthy premenopausal women, residing in western New York, 2005–2007. Methods: Women enrolled in the BioCycle Study ( n = 249, mean age 27.4 years and body mass index [BMI] 24.1 kg/m 2 ) completed a baseline food frequency questionnaire and provided blood samples to measure levels of mercury (Hg), lead (Pb), and cadmium (Cd). We used linear regression to examine associations between food intake and log-transformed toxic metals, adjusted for age, BMI, race, smoking, physical activity, and intakes of total energy, protein, fat, and fiber. Models were adjusted for false discovery rate. Results: Total fish intake ≥ 1 serving per day was associated with 54.7% (95% confidence interval [CI] 36.1, 75.9) higher Hg levels, compared to <1 serving. Specific fish intakes (i.e., canned tuna, fried fish, shellfish, white fish, and dark fish) were also associated with higher Hg levels. Though total meat intakes were not associated with Hg, intakes of lunch meat (28.1%), beef, pork, and lamb (21.0%), and chicken and turkey (43.5%) were associated with higher Hg levels, compared to no intake. Intakes of specific vegetables, including red pepper (17.4%), green beans (20.1%), summer (24.7%) and winter squash (19.3%), and garlic (18.5%) were associated with higher Hg. Total fruit intake ≥ 1 serving per day was also positively associated with Hg (18.7%, 95% CI 4.8, 34.5), compared to <1 serving, particularly with bananas (21.6%, >0 versus no intake). Compared to no intake, green pepper (11.8%) and cauliflower (9.9%) were positively associated with Pb, whereas apples were inversely associated with Pb (−14.6%). No associations were found between food intakes and Cd in our data. Conclusions: We found that intakes of certain foods are related to a higher blood level of toxic metals among reproductive aged women with metals level typical of the US population. Given the nutritional values of these food items, further research on food preparations (e.g., washing, packing) to reduce toxic metals exposure is needed. Funding Sources: Intramural Research Program, DIPHR, NICHD.